Bionomics of Anopheles (Nyssorhynchus) albimanus (Diptera: Culicidae) in two villages of the Wayúu people, Riohacha, La Guajira, Colombia - Airleth Sofía Díaz; Aura Isabel Sotelo; Catalina González-Uribe; Helena L. Brochero (Biomédica, 2017)
Introduction: Riohacha, capital of the department of La Guajira, reports the highest rates for malaria in the department, and the most vulnerable people are those of the Wayúu indigenous group. Objective: To describe some aspects of the bionomics of the Anopheles species in two Wayúu settlements. Materials and methods: Two sampling events were carried out during dry and rainy seasons in Marbacella and El Horno (Riohacha, La Guajira). Immature stages of Anopheles spp. were collected, and breeding sites were described. Adult mosquitoes were collected with human landing catches, Shannon traps and CDC traps. Results: All collected specimens were Anopheles albimanus. Biting activity occurred outdoors during all the night (n=7), while indoors, only two mosquitoes were captured between 18:00 and 20:00 hours. The positive breeding sites corresponded to jagüeyes (n=7, 38.8%), pools (n=2, 10.5%), and fishponds (n=2, 10.5%). The highest abundance of immature forms was found in the jagüeyes (n=25, 78%), which had pH values between 7.20 and 7.81 and a temperature of 25°C, and were located 150 m away from Wayúu homes. Conclusion: Anopheles albimanus was the only collected species found in water supply deposits in the villages Marbacella and El Horno. Given that the species is the main vector for malaria in the area, we suggest the implementation of a community-based entomological surveillance system which should respect Wayúu cosmology and routine activities such as fishing.